NOUNS IN ENGLISH – STRUCTURE, THEORY, LINGUISTIC RESEARCH, AND SCHOLARLY PERSPECTIVES - Inoyatulloyeva Nazokat Izzatullo qizi, (TADQIQOTLAR, 2026)
Annotation: This article provides a comprehensive and scholarly examination of nouns in English, exploring their structure, historical development, classifications, linguistic functions, and cognitive significance. It highlights theoretical perspectives from  leading  linguists,  including  Chomsky,  Crystal,  Aitchison,  Jespersen,  and Huddleston,  demonstrating  how  nouns  serve  as  core  lexical  categories,  semantic anchors,  and  essential  components  of  communication.  The  study  also  discusses irregular  plurals,  noun  phrases,  and  the  role  of  nouns  in  academic  and  cognitive development. Emphasis is placed on the interaction between grammatical structure and human cognition, showing that nouns not only label the world but also shape  how knowledge is organized and conveyed. This article underscores the centrality of nouns in English language structure, research writing, and formal communication.